TINJAUAN HUKUM ISLAM TERHADAP SISTEM “BAGI HASIL” PETANI BAWANG MERAH DI DESA BANJARSAWAH KECAMATAN TEGALSIWALAN KABUPATEN PROBOLINGGO - Mohammad Arifin; Reza Hilmy Luayyin; Muhammad Alfi Syahrin; Ahmad Indra Yani (LPPM STAI Muhammadiyah Probolinggo, 2022)
The increasing intensity of onion farmers is in line with the development of good agricultural land processing. Agricultural land in this rice field is managed in various ways, first is the owner of his own farmed rice field, second is the owner of rice fields renting land to others, third is the owner of rice fields in collaboration with people who have the ability to farm. Islam has provided a solution in utilizing agricultural land or rice fields, the form of cooperation can be by using two Fatwa DSN MUI in general, namely the mudharabah agreement if the working person is two people, namely the first party of the land owner and the second party of the farmer or land manager, but if the cooperation of more than 2 people can use the musyarakah agreement, the first party is the land owner, the second party of financiers and third parties of farmers. There are another 3 (three) islamic legal agreement systems that are focused on agriculture, namely musaqah, muzara'ah and mukharabah.The agreement applied by farmers in the village of Banjarsawah is an unnamed agreement (al 'uqud ghair al-musamma), this is allowed in Islam if no party is harmed, because in the agreement on Islamic economic law is certainly based on the principle of piety, ability, justice, equality or equality, honesty, written, usefulness or benefit for all those who do so.